1974
DOI: 10.1104/pp.53.6.875
|View full text |Cite
|
Sign up to set email alerts
|

Seed Aging: Chromosome Stability and Extended Viability of Seeds Stored Fully Imbided

Abstract: MATERIALS AND METHODS"Seeds" (fruits) of Lactuca sativa L. vars. Arctic King and Grand Rapids were obtained from Suttons Seeds Ltd., Reading, U. K. Batches of these seeds were placed in closed containers with separate vessels of sulfuric acid, water, or diluted sulphuric acid giving relative humidities of 0, 25, 50, 75, and 100% at 20 C in the container atmospheres (9). After 2 weeks, the moisture contents of the seed batches were determined, and the seeds were sealed into separate glass bottles. Other large b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0
3

Year Published

1980
1980
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(35 citation statements)
references
References 6 publications
1
31
0
3
Order By: Relevance
“…Seed vigour measures the potential for rapid, uniform seed germination under a wide range of field conditions (Bray 1997). Seeds deteriorate more rapidly at high MC levels and high temperatures than at lower levels (McDonald 1999), leading to genetic and structural damage (Villiers 1974). The vigour of seeds can be assessed using a variety of methods, including physiological and biochemical tests.…”
Section: Introductionmentioning
confidence: 99%
“…Seed vigour measures the potential for rapid, uniform seed germination under a wide range of field conditions (Bray 1997). Seeds deteriorate more rapidly at high MC levels and high temperatures than at lower levels (McDonald 1999), leading to genetic and structural damage (Villiers 1974). The vigour of seeds can be assessed using a variety of methods, including physiological and biochemical tests.…”
Section: Introductionmentioning
confidence: 99%
“…The initial slow hydration of the seeds probably allows for ordered rearrangement of the membrane before the inrush of water associated with imbibitions from the dry state, which might otherwise be too sudden and disruptive (Powell and Matthews 1977). Stored seeds in an imbibed state in which they remain metabolically active (Powell et al 1983(Powell et al , 1984 and helps to maintain their viability (Villiers 1974) to repair the membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Seed buried in the current field study survived at least 5 years, with higher rates of survival from seed buried below 200 mm than seed nearer the soil surface. Villiers (1974) suggested that the low metabolic rate experienced by dormant seeds in the soil seed bank enables seed, after hydration, to repair damage and detoxify. Therefore, wetdry cycling experienced in the soil seed bank might promote persistence.…”
Section: Seed Burialmentioning
confidence: 99%